Chapter 13. Gastrointestinal Model Construction (Computer Aided Drug Development, 2024)
AuthorDr. Anant Kumar PatelProfessor and HOD, Department of Pharmacology, Swami Vivekanand College of Pharmacy, Indore, Madhya Pradesh, IndiaAbstractGastrointestinal model construction represents a critical advancement in understanding digestive system physiology and drug absorption mechanisms. The development of both in vitro and in silico models has enabled detailed investigation of complex gastrointestinal processes. Physical models incorporate multiple compartments simulating different regions of the digestive tract, complete with pH gradients, enzymatic activities, and absorption surfaces. Advanced computational models integrate physiological parameters, fluid dynamics, and molecular interactions to predict drug behavior and nutrient absorption. Three-dimensional tissue engineering approaches create realistic intestinal epithelia, including functional tight junctions and metabolic enzymes. The incorporation of sensor technologies enables real-time monitoring of various parameters, including pH, dissolved oxygen, and metabolite concentrations. Machine learning algorithms enhance model predictions by analyzing complex datasets from multiple experiments. These sophisticated models serve as valuable tools for drug development, toxicology studies, and nutritional research, reducing the need for animal testing while providing detailed mechanistic insights. Recent developments include the integration of organ-on-chip technology and microfluidic systems, further improving the physiological relevance of these models.Keywords: Gastrointestinal Physiology: In Vitro Models: Computational Modeling: Tissue Engineering: Drug Absorption: Microfluidics: Bioreactor SystemsView PDF